Isolation of small SSEA-4-positive putative stem cells from the ovarian surface epithelium of adult human ovaries by two different methods - Virant-Klun, Irma; Skutella, Thomas; Hren, Matjaz; Gruden, Kristina; Cvjeticanin, Branko; Vogler, Andrej; Sinkovec, Jasna (BioMed research international, 2013)
The adult ovarian surface epithelium has already been proposed as a source of stem cells and germinal cells in the literature, therefore it has been termed the “germinal epithelium”. At present more studies have confirmed the presence of stem cells expressing markers of pluripotency in adult mammalian ovaries, including humans. The aim of this study was to isolate a population of stem cells, based on the expression of pluripotency-related stage-specific embryonic antigen-4 (SSEA-4) from adult human ovarian surface epithelium by two different methods: magnetic-activated cell sorting and fluorescence-activated cell sorting. Both methods made it possible to isolate a similar, relatively homogenous population of small, SSEA-4-positive cells with diameters of up to 4 μm from the suspension of cells retrieved by brushing of the ovarian cortex biopsies in reproductive-age and postmenopausal women and in women with premature ovarian failure. The immunocytochemistry and genetic analyses revealed that these small cells - putative stem cells - expressed some primordial germ cell and pluripotency-related markers and might be related to the in vitro development of oocyte-like cells expressing some oocyte-specific transcription factors in the presence of donated follicular fluid with substances important for oocyte growth and development. The stemness of these cells needs to be further researched.
Gesehen am 03.03.2022